1993
DOI: 10.1007/bf02769180
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-receptor interactions as an integrative mechanism in nerve cells

Abstract: Several lines of evidence indicate that interactions among transmission lines can take place at the level of the cell membrane via interactions among macromolecules, integral or associated to the cell membrane, involved in signal recognition and transduction. The present view will focus on this last subject, i.e., on the interactions between receptors for chemical signals at the level of the neuronal membrane (receptor-receptor interaction). By receptor-receptor interaction we mean that a neurotransmitter or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 126 publications
(72 citation statements)
references
References 232 publications
2
67
0
3
Order By: Relevance
“…Additional in vivo studies, which examined the interactions of clonidine (a partial agonist for a 2A -ARs) and neuropeptide Y (NPY; a 36 amino acid neurotransmitter) on sleep-wakefulness cycles and arterial blood pressure control in both normal and spontaneously hypertensive rats (Fuxe et al, 1989;Fuxe, 1990;Yang et al, 1994), further supported the existence of receptor-receptor interactions and their potential functional relevance. As a logical consequence for the indications of direct physical interactions between neuropeptide and monoamine receptors, the term heteromerization was introduced to describe a specific interaction between different types of GPCRs (Zoli et al, 1993). The concept of the GPCR heterodimer was later confirmed by studies reporting that two non-functional GPCR monomers, GABA B1 and GABA B2 , can assemble in signaling heterodimers at the cell surface to transmit the inhibitory effect of the g-aminobutyric acid (GABA) neurotransmitter (Marshall et al, 1999): when expressed alone, the GABA B1 receptor is retained in the endoplasmic reticulum, and is able to reach the cell surface and bind GABA only in the presence of its partner, the GABA B2 receptor.…”
Section: Box 1 Receptor Heterodimer and Receptor Mosaic Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional in vivo studies, which examined the interactions of clonidine (a partial agonist for a 2A -ARs) and neuropeptide Y (NPY; a 36 amino acid neurotransmitter) on sleep-wakefulness cycles and arterial blood pressure control in both normal and spontaneously hypertensive rats (Fuxe et al, 1989;Fuxe, 1990;Yang et al, 1994), further supported the existence of receptor-receptor interactions and their potential functional relevance. As a logical consequence for the indications of direct physical interactions between neuropeptide and monoamine receptors, the term heteromerization was introduced to describe a specific interaction between different types of GPCRs (Zoli et al, 1993). The concept of the GPCR heterodimer was later confirmed by studies reporting that two non-functional GPCR monomers, GABA B1 and GABA B2 , can assemble in signaling heterodimers at the cell surface to transmit the inhibitory effect of the g-aminobutyric acid (GABA) neurotransmitter (Marshall et al, 1999): when expressed alone, the GABA B1 receptor is retained in the endoplasmic reticulum, and is able to reach the cell surface and bind GABA only in the presence of its partner, the GABA B2 receptor.…”
Section: Box 1 Receptor Heterodimer and Receptor Mosaic Conceptsmentioning
confidence: 99%
“…through allosteric interactions) in the plasma membrane (Agnati et al, 1982;Zoli et al, 1993). It was proposed that an RM functions as an integrated unit with unique signaling properties that are modulated by receptor-receptor allosteric interactions.…”
Section: Box 1 Receptor Heterodimer and Receptor Mosaic Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1993 (Zoli et al, 1993), the hypothesis was introduced that the molecular mechanism for these large numbers of intramembrane receptor/receptor interactions among GPCR could be the formation of heteromeric complexes, the simplest being a heterodimer. This concept was based on the indication at the time that dimerization upon agonist activation may be a general phenomenon essential for receptor activation (Hollenberg, 1991), the best example being the dimerization of tyrosine kinase receptors (Schlessinger 1988(Schlessinger , 2000Helldin 1995).…”
mentioning
confidence: 99%
“…Thus, it was assumed that GPCR exist mainly as homodimers that interact with other types of homodimers to form heterodimers. The relative proportions of homo-and heterodimers would be determined by the concentrations of the two transmitters, the density of the two receptors and their distribution patterns, and the unique features of each receptor/receptor interaction (Zoli et al, 1993). In fact, early evidence obtained on purified GPCR by, e.g., Venter and Fraser (1983) and Conn et al (1982) indicated that the functional GPCR were in a dimeric state.…”
mentioning
confidence: 99%